A composite liquid-absorbing core and its manufacturing method and application
By covering the nanoporous layer on the inner wall surface of the trench of the liquid absorbent core, the problems of large flow resistance, complex process and high cost of the existing liquid absorbent core are solved, and the balance between large capillary pressure and small flow resistance is achieved, reducing thermal resistance and manufacturing costs.
Patent Information
- Application Number
- CN202111175491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-09
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-10-09
AI Technical Summary
While the existing liquid absorbent core achieves large capillary pressure and small flow resistance, there are problems such as large flow resistance, complex process and high cost.
A composite liquid absorbent core structure is adopted, including a trench and a nanoporous layer. The nanoporous layer covers the inner wall surface of the trench, and the trench is formed by ablation by short pulse laser, and ablation products are deposited into a nanoporous layer using a unidirectional gas flow.
The balance of large capillary pressure and small flow resistance is achieved, reducing the thermal resistance of the heat pipe and the heat-hosing plate, simplifying the process and reducing manufacturing costs.
Smart Images

Figure CN113983842B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of heat dissipation devices, and in particular to a composite liquid absorbent core and a manufacturing method and application thereof. Background Art
[0002] Both heat pipes and vapor chambers are heat transfer elements that use the phase change process of the medium to achieve rapid heat conduction. Among them, the heat pipe is a one-dimensional heat transfer device, generally in a tubular or flat shape, which uses the liquid working medium to evaporate at the evaporation end of the heat pipe and take away heat. The heat is the latent heat of evaporation of the working medium. The steam flows from the central channel to the condensation section of the heat pipe, condenses into liquid, and releases latent heat at the same time. Under the action of capillary force, the liquid flows back to the evaporation section. The vapor chamber is a two-dimensional heat transfer planar device, generally a flat plate structure with a large area. The working medium also evaporates at the evaporation end, and after condensing at the condensation end, it flows back to the evaporation end through the internal capillary structure.
[0003] The heat dissipation performance of heat pipes and vapor chambers is mainly determined by the internal wicks. Currently, common wick structures include wire mesh, sintered, and grooved wicks. An ideal wick requires a large capillary pressure and a small flow resistance, but it is difficult to achieve both of these properties at the same time. Generally speaking, wire mesh and sintered wicks have large capillary pressures, but also large flow resistances, while grooved wicks have small capillary pressures and flow resistances.
[0004] In order to overcome the above contradictions, the following solutions are currently available: 1) The related technology proposes a composite absorbent core sintered from copper powder and copper fiber and a method for manufacturing the same. The absorbent core uses the guiding effect of the copper fiber to reduce the flow resistance of the sintered absorbent core; 2) There is also a related technology that proposes a toothed composite absorbent core and a method for preparing the same. The absorbent core is made by sintering a mixture of copper powder and copper fiber on a copper tube wall with microgrooves. Due to the presence of the microgrooves at the bottom, the flow resistance can be reduced; 3) There is another related technology that proposes a porous channel and microfiber composite absorbent core and a method for manufacturing the same, which includes a porous matrix formed by sintering metal powder, a parallel channel structure formed on the surface of the porous matrix, and needle-like microfibers on one side of the channel wall.
[0005] The above methods still have problems such as large flow resistance, complex process and high cost. For example, it is difficult to achieve uniform and continuous arrangement of fibers through the solution of copper powder and fiber composite, which may cause local flow resistance to increase; the preparation of liquid absorbent core with groove and sintered structure composite generally requires high temperature sintering, secondary processing of grooves and other different processes, which greatly increases the processing cost. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a composite liquid absorbent core having a large capillary pressure and a small flow resistance.
[0007] At the same time, the invention also provides a manufacturing method and application of the composite liquid-absorbing core.
[0008] Specifically, the present invention adopts the following technical solutions:
[0009] A first aspect of the present invention is to provide a composite liquid absorbent core, the composite liquid absorbent core comprising a groove and a nanoporous layer, wherein the nanoporous layer covers the inner wall surface of the groove.
[0010] The composite liquid-absorbent core according to the first aspect of the present invention has at least the following beneficial effects:
[0011] The nanoporous structure in the composite absorbent core can provide a large capillary pressure, while the groove structure can effectively reduce the backflow resistance. Under the combined effect of the two, the composite absorbent core has a large capillary pressure and a small flow resistance.
[0012] In some embodiments of the present invention, the nanoporous layer covers at least one side of the inner wall surface of the groove, preferably covers one side of the inner wall surface of the groove. The nanoporous layer can completely cover the inner wall of one side of the groove, or only cover a partial area of the inner wall of one side of the groove. The nanoporous layer covers the inner wall surface of one side of the groove, while the inner wall of the other side is not covered, so as to avoid excessive coverage causing an increase in flow resistance.
[0013] In some embodiments of the present invention, the aspect ratio of the groove is 0.2 to 5. The aspect ratio refers to the ratio of the depth of the groove to the top width.
[0014] In some embodiments of the present invention, the top width of the groove is 20-80 μm, and the depth is 20-100 μm.
[0015] In some embodiments of the present invention, the cross-sectional shape of the groove includes at least one of (quasi) V-shaped, (quasi) T-shaped, rectangular, and arc-shaped, preferably including (quasi) V-shaped and (quasi) T-shaped. The (quasi) V-shaped groove structure is characterized in that the top width of the groove is greater than the bottom width, the top width is 20 to 80 μm, and the bottom width is not greater than 10 μm; the (quasi) T-shaped groove structure is characterized in that the top width of the groove is greater than the bottom width, the top width is 20 to 80 μm, and the bottom width is 10 to 60 μm.
[0016] In some embodiments of the present invention, the thickness of the nanoporous layer is 50 to 10000 nm; the diameter of the nanopores inside the nanoporous layer is 5 to 500 nm.
[0017] In some embodiments of the present invention, the grooves are disposed on a surface of a substrate. The substrate is a metal substrate, including at least one of copper, copper alloy, and stainless steel. The grooves are periodically arranged on the surface of the substrate.
[0018] In some embodiments of the present invention, the element composition of the nanoporous layer may be the same as that of the substrate, or may only contain some elements in the substrate, and the element ratio may be different from that of the substrate, or may be a mixture of some or all elements in the substrate plus oxygen.
[0019] The second aspect of the present invention is to provide a method for manufacturing the composite liquid-absorbing core, comprising the following steps:
[0020] The substrate surface is ablated by a phase explosion mechanism to form a groove, and the ablation product is deposited on the inner wall surface of the groove;
[0021] The ablated sample is subjected to reduction sintering to obtain a composite liquid-absorbing core.
[0022] Phase explosion means that the material in the ablated area of the substrate surface is mainly ejected from the substrate surface in the form of a mixture of vapor and nano droplets. The present invention ablates the substrate surface by a phase explosion mechanism to form grooves. During the ablation process, a mixture of vapor and nano droplets (i.e., ablation products) can be generated. The mixture of vapor and nano droplets can form a denser nanoporous structure through deposition, reduction and sintering.
[0023] In some embodiments of the present invention, the ablation method includes high repetition rate laser scanning, and the pulse energy density of the laser is greater than the phase explosion threshold of the substrate. For example, for copper and copper alloy substrates, the laser pulse energy flux density reaching the substrate surface should be greater than 1J / cm 2 For stainless steel substrates, the laser pulse energy density reaching the substrate surface should be greater than 0.3J / cm 2 When the laser pulse energy flux density is less than or equal to the phase explosion threshold of the substrate, the material in the laser scanning area will be mainly ablated and removed by mechanisms such as photo-stripping, and a large amount of vapor and nano-droplet mixture cannot be generated, and an effective nanoporous structure cannot be deposited.
[0024] In some embodiments of the present invention, the pulse repetition frequency (repetition rate) of the laser is not less than 100 kHz, such as 100-500 kHz, 200-400 kHz or other repetition rates. Too low a repetition rate will result in the ablation product being unable to form effective enrichment and difficult to deposit near the laser irradiation area.
[0025] The half-width of the laser pulse is less than 1 ns.
[0026] In some embodiments of the present invention, the laser is an ultrashort pulse laser, and an ultrashort pulse laser refers to a laser pulse with a pulse half-width ≤ 1 nanosecond.
[0027] In some embodiments of the present invention, the method for depositing the ablation products on the inner wall surface of the groove is to apply a unidirectional airflow (referring to an airflow flowing from one direction to another direction) during the ablation process, so that the ablation products move along the airflow and are deposited on the inner wall of the groove. The ablation products are high-temperature products ejected in the form of a mixture of vapor and nano-droplets after the laser irradiates the surface of the substrate and causes a phase explosion, and the temperature decreases with the increase of the movement distance. Under the action of high repetition rate pulses, a large number of ablation products are effectively enriched, and at the same time, affected by the surface airflow, while being ejected upward from the surface of the substrate, they move in the direction of the airflow flow, and after being hindered by the inner wall of the groove during the movement, they adhere to the inner wall of the groove to form a nanoporous structure; the ablation products that subsequently reach the inner wall of the groove continue to adhere to the surface of the nanoporous structure that has been formed, and finally form a nanoporous layer of a certain thickness.
[0028] In some embodiments of the present invention, the flow direction of the gas flow is at an angle of 0° to 45° to the substrate surface, and at an angle of 45° to 90° to the ablation direction (i.e., the laser scanning direction). By adding gas flow and controlling the direction of the gas flow, the ablation product can be successfully deposited on the inner wall surface of the groove. If the direction of the gas flow is improperly controlled, the deposition process of the ablation product will be affected, and the capillary pressure will be reduced. The gas flow can be any gas, such as air flow, nitrogen flow, argon flow, etc.; the flow rate of the gas flow is 0.1 to 100 m / s.
[0029] In some embodiments of the present invention, the reduction sintering temperature is 400-1200°C, and the reduction sintering time is 30-180 minutes. In actual operation, the temperature can be raised to 400-700°C at a rate of 200-800°C / h in a reducing atmosphere, and then kept warm for 20-100 minutes, and then kept warm at 700-1000°C for 10-60 minutes, so that the deposited ablation products are partially reduced and sintered to form a nanoporous layer. The nanoporous structure formed by the deposition of the ablation products on the inner wall of the groove is relatively loose, and there are a large number of oxidation products inside, which need to be reduced and sintered to form the final nanoporous layer.
[0030] In some embodiments of the present invention, the reducing atmosphere refers to an atmosphere containing a reducing gas, and the reducing gas includes at least one of hydrogen and carbon monoxide. For example, a mixed gas of hydrogen and argon can be used to form a reducing atmosphere, wherein the flow rate of argon can be set to 1% to 20%, preferably 5% to 10% of the argon. In actual operation, the reducing atmosphere can be selected and adjusted according to actual conditions.
[0031] A third aspect of the present invention is to provide a heat pipe or a vapor chamber, wherein the heat pipe or the vapor chamber comprises the composite liquid wick.
[0032] The present invention also provides application of the composite liquid-absorbing core in manufacturing servers, computers, mobile phones or lighting equipment.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The composite liquid wick has a groove structure and a nanoporous layer. The nanoporous layer can effectively increase the capillary pressure, and the groove structure can effectively reduce the flow resistance. At the same time, the evaporation and condensation processes of the working medium in the nanoporous layer will be increased, thereby effectively reducing the thermal resistance of the heat pipe and heat spreader device.
[0035] (2) The groove structure is directly obtained by short-pulse laser ablation, and secondary deposition is achieved through the movement of the ablation product in the airflow field to obtain a nanoporous structure. The process is simple and controllable. No special mold is required to prepare the special-shaped structure. The formation principle of the unidirectional airflow field is simple and easy to implement, which is suitable for mass production. The obtained nanoporous structure is easy to reduce and sinter, which reduces the sintering temperature and insulation time of the subsequent sintering process, which is conducive to reducing manufacturing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a schematic diagram of three parallel line arrays of Example 1;
[0037] Figure 2 is a partial cross-sectional profile diagram of the composite absorbent core of Example 1;
[0038] Figure 3 It is a partial top view of the composite absorbent core of Example 1;
[0039] Figure 4 is a partial cross-sectional view of the composite absorbent core of Example 2;
[0040] Figure 5 It is a partial cross-sectional view of the T-groove wick of Comparative Example 1;
[0041] Figure 6 It is a partial cross-sectional view of the V-groove absorbent core of Comparative Example 2;
[0042] Figure 7 1 is the liquid level climbing height curve of the liquid absorbent core of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0043] The technical scheme of the present invention is further described below in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources; the processes used, unless otherwise specified, all adopt conventional processes in the art.
[0044] Example 1
[0045] The size is 70×70×1mm 3 The copper plate is scanned by short pulse laser in the air, and the scanning area is 68×68mm 2 The laser and scanning parameters are: laser pulse half-width 290fs, wavelength 515nm, repetition frequency 200kHz, laser energy flux density reaching the workpiece surface 2J / cm 2 , continuous parallel scanning. The scanning line pattern is a periodic array of parallel lines. Figure 1 The figure shows a schematic diagram of three parallel line arrays, with a spacing of 10 μm between parallel lines and a spacing of 30 μm between arrays. The scanning speed is 10 mm / s and the number of scans is 1. A unidirectional airflow field is applied during the scanning process. The unidirectional airflow field is formed by a high-speed micro fan placed near the sample. The angle between the airflow direction and the sample surface and the laser scanning direction is controlled by controlling the relative position of the fan and the sample, and the air flow rate is controlled by controlling the fan speed. In this example, the angle between the airflow direction and the sample surface is 20°, the angle with the laser scanning direction is 90°, and the airflow velocity is 10 m / s.
[0046] After scanning, the sample was fixed with a fixture and placed in a reducing atmosphere sintering furnace for heating at a heating rate of 500°C / h. The atmosphere was a mixture of hydrogen and argon, where the flow rate of hydrogen was 5% of that of argon. After heating to 500°C, it was kept warm for 30 minutes, and then kept warm at 700°C for 20 minutes. After completion, the furnace was cooled to room temperature, the sample was taken out and the fixture was removed, and the composite liquid wick on the surface of the copper plate was obtained.
[0047] Figure 2 , Figure 3 The figure shows the partial cross-sectional profile and top view of the composite absorbent core. The composite absorbent core consists of a T-shaped groove and a nanoporous layer attached to the inner wall of one side of the groove; the groove has a top width of 60 μm, a bottom width of 30 μm, and a depth of about 70 μm; the thickness of the nanoporous layer is about 10 μm, and the diameter of the internal nanopores is mainly distributed in the range of 5 to 50 nm.
[0048] Example 2
[0049] The size is 40×50×1mm 3 The surface of C5191 phosphor bronze plate is scanned by short pulse laser in air, and the scanning area size is 38×48mm 2The laser and scanning parameters are: laser pulse half-width 10ps, wavelength 1030nm, repetition frequency 400kHz, laser energy flux density reaching the workpiece surface 1.5J / cm 2 , continuous parallel scanning, scanning line spacing of 30μm, scanning speed of 40mm / s, repeated scanning 10 times. A unidirectional airflow field is applied during the scanning process. The unidirectional airflow field is achieved by placing a vacuum tube near the sample. The vacuum tube is connected to a vacuum cleaner with a filter. The angle between the airflow direction and the sample surface and the laser scanning direction is controlled by controlling the relative position of the vacuum tube and the sample. The air flow rate is controlled by the power of the vacuum cleaner. In this example, the angle between the airflow direction and the sample surface is 0°, the angle with the laser scanning direction is 90°, and the airflow rate is 5m / s.
[0050] After scanning, the sample was fixed with a fixture and placed in a reducing atmosphere sintering furnace for heating at a heating rate of 400°C / h. The atmosphere was a mixture of hydrogen and argon, where the flow rate of hydrogen was 10% of that of argon. After heating to 500°C, it was kept warm for 30 minutes, and then kept warm at 700°C for 10 minutes. After completion, the furnace was cooled to room temperature, the sample was taken out and the fixture was removed, and the composite liquid wick on the surface of the phosphor copper plate was obtained. Figure 4 This is a partial cross-sectional profile of the composite absorbent core.
[0051] Comparative Example 1
[0052] The size is 70×70×1mm 3 The copper plate is scanned by short pulse laser in the air, and the scanning area is 68×68mm 2 The laser and scanning parameters are: laser pulse half-width 290fs, wavelength 515nm, repetition frequency 200kHz, laser energy flux density reaching the workpiece surface 2J / cm 2 , continuous parallel scanning, the scanning line pattern is a periodic parallel line array, the spacing between parallel lines is 10μm, and the spacing between arrays is 30μm. The scanning speed is 10mm / s, and the number of scans is 1 time. A unidirectional airflow field is applied during the scanning process. The unidirectional airflow field is formed by a high-speed micro fan placed near the sample. The angle between the airflow direction and the sample surface and the laser scanning direction is controlled by controlling the relative position of the fan and the sample, and the air flow rate is controlled by controlling the fan speed. In this example, the angle between the airflow direction and the sample surface is 70°, the angle with the laser scanning direction is 0°, and the airflow rate is 10m / s. After the scanning is completed, it is placed in a reducing atmosphere sintering furnace, and the sintering process is the same as implementation 1. After sintering, a T-groove liquid wick on the surface of the copper plate is obtained.
[0053] Figure 5The figure shows a partial cross-sectional view of a T-groove wick. Since the unidirectional airflow applied during the processing in this example is at an angle of 70° to the sample surface and 0° to the laser scanning direction, the laser ablation product cannot be deposited on the inner wall of the groove, and the formed structure only has the groove morphology.
[0054] Comparative Example 2
[0055] The size is 40×50×1mm 3 C5191 phosphor bronze plate, the surface of the stainless steel plate is scanned by short pulse laser in the air, the scanning area size is 38×48mm 2 The laser and scanning parameters are: laser pulse half-width 10ps, wavelength 1030nm, repetition frequency 400kHz, laser energy flux density reaching the workpiece surface 1.5J / cm 2 , continuous parallel scanning, scanning line spacing of 30μm, scanning speed of 40mm / s, repeated scanning 10 times. A unidirectional airflow field is applied during the scanning process. Figure 6 As shown, the unidirectional airflow field is realized by placing a vacuum tube near the sample, and the vacuum tube is connected to a vacuum cleaner with a filter. The angle between the airflow direction and the sample surface and the laser scanning direction is controlled by controlling the relative position of the vacuum tube and the sample, and the flow rate of the air flow is controlled by the power of the vacuum cleaner. In this example, the angle between the airflow direction and the sample surface is 80°, the angle with the laser scanning direction is 10°, and the airflow velocity is 5m / s. After the scanning is completed, it is placed in a reducing atmosphere sintering furnace, and the sintering process is the same as that of implementation 2. After the sintering is completed, a V-groove liquid-absorbing core on the surface of the phosphor bronze plate is obtained.
[0056] Figure 6 The figure shows a partial cross-sectional view of a V-groove wick. Since the unidirectional airflow applied during the processing in this example is at an angle of 80° to the sample surface and 10° to the laser scanning direction, the laser ablation product cannot be deposited on the inner wall of the groove, and the formed structure only has the groove morphology.
[0057] Performance Testing
[0058] (1) Characterization of capillary rise performance
[0059] The capillary rise performance of the wick was characterized as follows:
[0060] The prepared composite liquid-absorbing core sample is fixed on a fixed frame that can be moved up and down, a container filled with deionized water is placed under the sample, and the sample is slowly moved downward until it touches the liquid surface of the deionized water, and the height of the liquid level in the sample is recorded by a high-speed camera.
[0061] The liquid level climbing height curves of the composite liquid absorbent cores of Example 1 and Comparative Example 1 are as follows: Figure 7The results show that the composite absorbent core prepared in Example 1 only takes 7 seconds to climb 7 cm, while the V-shaped groove structure prepared in Comparative Example 1 takes as long as 12 seconds to climb 7 cm. The capillary climbing speed of the composite absorbent core in Example 1 is 50% higher than that of the V-shaped groove structure prepared in Comparative Example 1.
Claims
1. A composite liquid-absorbing core, characterized in that: The composite liquid-absorbing core comprises a groove and a nanoporous layer, wherein the nanoporous layer covers the inner wall surface of the groove; the thickness of the nanoporous layer is 50-10000 nm; the diameter of the nanopores inside the nanoporous layer is 5-500 nm; The composite liquid-absorbing core is prepared by a method comprising the following steps: ablating the surface of the substrate by a phase explosion mechanism to form a groove, and depositing the ablation product on the inner wall surface of the groove; The ablated sample is subjected to reduction sintering to obtain a composite liquid-absorbing core; The method for achieving the ablation includes laser scanning, wherein the pulse energy density of the laser is greater than the phase explosion threshold of the substrate; the pulse repetition frequency of the laser is not less than 100 kHz; The method for depositing the ablation products on the inner wall surface of the groove is to apply a unidirectional airflow during the ablation process, so that the ablation products move along the airflow and are deposited on the inner wall of the groove; the flow direction of the airflow is at an angle of 0° to 45° with the surface of the substrate, and at an angle of 45° to 90° with the laser scanning direction.
2. The composite absorbent core according to claim 1, characterized in that: The nanoporous layer covers at least one inner wall surface of the groove.
3. The composite absorbent core according to claim 1, characterized in that: The aspect ratio of the groove is 0.2-5.
4. The method for manufacturing the composite liquid-absorbing core according to any one of claims 1 to 3, characterized in that: The steps include: The substrate surface is ablated by a phase explosion mechanism to form a groove, and the ablation product is deposited on the inner wall surface of the groove; The ablated sample is subjected to reduction sintering to obtain a composite liquid-absorbing core.
5. The method for manufacturing the composite liquid-absorbing core according to claim 4, characterized in that: The half-width of the laser pulse is less than 1 ns.
6. A heat pipe or a vapor chamber, characterized in that: The heat pipe or vapor chamber comprises the composite liquid wick according to any one of claims 1 to 3.
7. Use of the composite liquid-absorbing core according to any one of claims 1 to 3 in manufacturing servers, computers, mobile phones or lighting equipment.
Citation Information
Patent Citations
Groove and microstructure composite liquid absorption core and manufacturing method thereof
CN105091648A
Compound ditch slot type imbibition core of flat plate heat pipe
CN206095014U